HPLC ESTIMATION AND FORMULATION OF FAST DISSOLVING RAMIPRIL TABLET - Mithileshwar Tiwari, Neha Sodiyal, Shivanand Patil (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
The aim of the study was to formulate and develop method for the simultaneous estimation of fast dissolving ramipril tablet formulation using HPLC. The angle of repose of formulation F1 to F9 was determined to be 25.3, 25.1, 25.2, 25.4, 25.1, 25.0, 25.3, 25.4 and 25.6 respectively which indicates the flow of granules is good. The bulk density, Tapped density of powder (from formulation F1 to F9) was determined was found to be 0.45g/cc, 0.45g/cc, 0.43g/cc, 0.58g/cc, 0.45 g/cc,0.55 g/cc, 0.43 g/cc, 0.55 g/cc, 0.53 g/cc and 0.53g/cc, 0.53g/cc, 0.51g/cc, 0.68g/cc, 0.53 g/cc,0.62 g/cc, 0.51 g/cc, 0.65 g/cc, 0.60 g/cc respectively. The Carr’s inddex was found to be 17.8, 17.8, 18.6, 17.2, 17.8, 12.7, 18.6, 18.2, 13.2 respectively, indicating F6 have lowest value i.e 12.7, thus it has better flow of powder than other formulation. The Hausner's ratio of formulation (F1-F9) was found to be 1.18, 1.18, 1.19, 1.17, 1.18, 1.13, 1.19, 1.18, and 1.13 respectively indicating formulation F6 and F9 have the lowest value (i.e. 1.13) and formulation F3 & F7 had highest value (i.e. 1.19), so formulation F6 and F9 has greater flow of powder among all these formulation., the thickness was around 3 and hardness was found to be 1.5 kg/cm. the friability of tablet was < 1%. The dissolution profile of formulation F1 to F9 was determined was found to be 96.35%, 95.21%, 97.26%, 94.25%, 93.91%, 95.0%, 93.09%, 90.58% and 101.55% respectively. From above data The formulation F3 (contain Polyethylene glycol 4000at greater amount), formulation F6 (containing PVK-30at greater amount), formulation F7, F8 and F9 (F9 (containing both Crosspovidone, MCC and Sodium glycolate)Crosspovidone) shows better release of drug among other formulation. The active content of each formulation was determined the found to be 98.07%, 94.70%, 96.39%, 96.40%, 96.45%, 98.57%, 97.88%, 98.08% and 102.5% from formulation F1 to F9 respectively.